T-cell receptor excision circle levels and safety of paediatric immunization: A population-based self-controlled case series analysis. Issue 6 (3rd June 2018) - Wilson, Kumanan; Duque, Daniel Rodriguez; Murphy, Malia S.Q; Hawken, Steven; Pham-Huy, Anne; Kwong, Jeffrey; Deeks, Shelley L.; Potter, Beth K.; Crowcroft, Natasha S.; Bulman, Dennis E.; Chakraborty, Pranesh; Little, Julian
ABSTRACT: T-cell receptor excision circle levels are a surrogate marker of T-cell production and immune system function. We sought to determine whether non-pathological levels of infant T-cell receptor excision circles were associated with adverse events following immunization. A self-controlled case series design was applied on a sample of 231, 693 children who completed newborn screening for severe combined immunodeficiency in Ontario, Canada between August 2013 and December 2015. Exposures included routinely administered pediatric vaccines up to 15 months of age. Main outcomes were combined health services utilization for recognized adverse events following immunization. 1, 406, 981 vaccination events were included in the final dataset. 103, 007 children received the Pneu-C-13 or Men-C-C vaccine and 97, 998 received the MMR vaccine at 12 months of age. 67, 725 children received the varicella immunization at 15 months. Our analysis identified no association between newborn T-cell receptor excision circle levels and subsequent health services utilization events following DTa-IPV-Hib, Pneu-C-13, and Men-C-C vaccinations at 2-month (RI 0.94[95%CI 0.87-1.02]), 4-month (RI 0.82[95%CI 0.75-0.9]), 6-month (RI 0.63[95%CI 0.57-0.7]) and 12-month (RI 0.49[95%CI 0.44-0.55]). We also found no trends in health services utilization following MMR (RI 1.43[95%1.34-1.52]) or varicella (RI 1.14[95%CI 1.05-1.23]) vaccination. Our findings provide further support for the safety of pediatric vaccinations.